2015
DOI: 10.5858/arpa.2014-0471-oa
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-375 Suppresses Extracellular Matrix Degradation and Invadopodial Activity in Head and Neck Squamous Cell Carcinoma

Abstract: Context Head and neck squamous cell carcinoma (HNSCC) is a highly invasive cancer with an association with locoregional recurrence and lymph node metastasis. We have previously reported that low microRNA-375 (miR-375) expression levels correlate with poor patient survival, increased locoregional recurrence, and distant metastasis. Increasing miR-375 expression in HNSCC cell lines to levels found in normal cells results in suppressed invasive properties. HNSCC invasion is mediated in part by invadopodia-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 97 publications
5
18
0
Order By: Relevance
“…Deregulated miR-375 has been identified in numerous cancer types, including laryngeal squamous cell carcinoma (23), head and neck squamous cell carcinoma (24), prostate cancer (25), hepatocellular carcinoma (26), lung cancer (27) and breast cancer (28). Wu et al (29) examined the circulating miR profile in patients with breast cancer by deep sequencing all circulating small RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Deregulated miR-375 has been identified in numerous cancer types, including laryngeal squamous cell carcinoma (23), head and neck squamous cell carcinoma (24), prostate cancer (25), hepatocellular carcinoma (26), lung cancer (27) and breast cancer (28). Wu et al (29) examined the circulating miR profile in patients with breast cancer by deep sequencing all circulating small RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…SCC‐25 and SCC‐61 cells degraded more ECM and formed more degrading and total invadopodia than the SCC‐47 and SCC‐104 cells, while SCC‐1 cells were only significantly greater when compared to SCC‐104 cells (Figure B‐D). These differences are consistent with previous reports of invadopodia activity by these cell lines (except SCC‐104 cells which have not previously been reported to form invadopodia to our knowledge) …”
Section: Resultssupporting
confidence: 93%
“…Because HPV + HNSCC has higher rates of metastasis, we first evaluated invadopodia activity in established HPV − and HPV + HNSCC cell lines because the ability to degrade the ECM is an important component of invasion (Figure A). HPV − SCC‐25, SCC‐61, and SCC‐1 cells are frequently used as cell line models for studying invadopodia . HPV + SCC‐47 and SCC‐104 cells are common cell line models for studying the effects of HPV‐16 .…”
Section: Resultsmentioning
confidence: 99%
“…17 An increasing number of studies have shown that the biological functions of miRNAs are highly correlated with cervical cancer. 1,2 miR-375 was first discovered in the pancreas; however, recent studies have found that the expression of miR-375 is downregulated in many cancers, such as esophageal squamous cell carcinoma, 18 head and neck cancer, 19 laryngeal squamous cell carcinoma, 20 and oral cancer. 21 Wang et al 12 examined the expression of miR-375 in 170 cervical cancer tissue specimens and 68 normal cervical tissue specimens using stem-loop quantitative PCR and found that compared with the 68 normal tissues, the expression of miR-375 in the cervical cancer tissues was significantly decreased by 4.45-fold.…”
Section: Discussionmentioning
confidence: 99%